Quantification of complex precore mutations of hepatitis B virus by SimpleProbe real time PCR and dual melting analysis - Nie, Hui (2011)
BACKGROUND: Hepatitis B virus (HBV) precore G1896A mutation is associated with Hepatitis B e antigen (HBeAg) seroconversion. This mutation and the adjacent G1899A mutation also appear to associate with increased risk of hepatocellular carcinoma. Quantitative mutant dynamics may help determine the potential of these mutants as clinical biomarkers. However, a reliable method to quantify either mutant is not available, partly because the viral genome has polymorphisms in general and the precore mutations are complex. OBJECTIVES: (1) To develop a reliable and ultrasensitive assay for the quantification of HBV G1896A and/or G1899A mutants. (2) To obtain preliminary data on the quantities of the precore mutants in patients. STUDY DESIGN: A SimpleProbe real time PCR assay was developed to quantify the HBV precore mutants. Dual melting analysis and a primer-probe partial overlap approach were used to increase detection accuracy. A wild-type selective PCR blocker was also developed to increase mutant detection sensitivity. RESULTS: The assay correctly identified the precore sequence from all 62 patient samples analyzed. More than 97% of precore sequences in the GenBank can be recognized. Mutant detection sensitivity reached 0.001% using a wild type-selective PCR blocker. At least one precore mutant can be detected from all 20 HBeAg-positive individuals who were negative for precore mutations by DNA sequencing. CONCLUSIONS: The reliability of this ultrasensitive mutation quantification assay was demonstrated. The same approaches may be useful for the detection of other clinically significant mutations. Evolution of the precore mutants warrants further studies.